(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To evaluate the advantages of combined motor and sensory evoked potential monitoring during scoliosis surgery. Methods: We performed and analyzed the records of 107 (83 Female (77.5%) and 24 male (22.4%) Scoliosis surgery patients with Transcranial electric motor evoked potential and somatosensory evoked potential performed at spine surgery center, Ghurki Trust Teaching Hospital Lahore. Mean age was 14.7 years. Patients who showed significant up to (45%) in baseline signals loss unilateral or bilateral limbs during surgical intervention in scoliosis surgery under total intravenous anesthesia is included. Results: Motor Evoked Potentials and Somato-Sensory Evoked Potenials of 107 patients in intraoperative neurophysiological monitoring were performed jointly. 21 (19.6%) patients have mark or significant changes in baseline signals on transcranial motor evoked potentials. Seventeen 17 (15.8%) Patients have complete return of baseline signals after surgical intervention by surgeon, whereas 04 (3.73%) patients have return of motor signals after 14 hours of surgery. Transcranial electric motor evoked potentials monitoring was 100% specific and 100% sensitive, however Somatosensory evoked potential was 100% specific and 84% sensitive. Conclusions: MEPs and SSEPs, in combination gives accurate and correct information of any surgical insult and neurology in real time during Scoliosis surgery.